Type II collagen C2C epitope in human synovial fluid and serum after knee injury – associations with molecular and structural markers of injury. Issue 9 (September 2015) - Kumahashi, N.; Swärd, P.; Larsson, S.; Lohmander, L.S.; Frobell, R.; Struglics, A.
Summary: Purpose: Investigate in a cross-sectional study time-dependent changes of synovial fluid type II collagen epitope C2C concentrations after knee injury and correlate to other joint injury biomarkers. Methods: Synovial fluid samples were aspirated between 0 days and 7 years after injury ( n  = 235). Serum was collected from 71 of the knee injured patients. Synovial fluid from 8 knee-healthy subjects was used as reference. C2C was quantified by immunoassay and structural injury was determined from magnetic resonance images (MRI) of the injured knee acquired 1–38 days after injury ( n  = 98). Additional joint injury biomarker results were from earlier investigations of the same samples. Results: Synovial fluid C2C concentrations were higher in injured knees than in knees of reference subjects from 1 day up to 7 years after injury. C2C concentrations in synovial fluid and serum were correlated ( r  = 0.403, P  < 0.001). In synovial fluid from subjects early after injury (0–33 days), C2C concentrations were correlated with cross-linked C-telopeptide of type II collagen ( r  = 0.444, P  = 0.003), ARGS-aggrecan ( r  = 0.337, P  < 0.001), osteocalcin ( r  = 0.345, P  < 0.001), osteopontin ( r  = 0.371, P  < 0.001) and IL-8 ( r  = −0.385, P  < 0.001), but not with structural joint injury as visualized on MRI. Conclusion: The increased levels of synovial fluid C2C after injury, together with the associations seen with several other injury-related biomarkers, suggest that an acute knee injury is associated with an immediate and sustained local degradation of type II collagen.